Family Resilience Strategies in the Contemporary Era: A Comparative Analysis of Al-Azhar and Ibn Katsir’s Tafsir on Surah At-Tahrim Verse 6 - Nasrullah, Muhamad; Indarti, Fantri; Ghufrani, Azzam (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research explores the critical role of family resilience in addressing the challenges of the contemporary era, characterized by shifting values, a consumptive lifestyle, and the erosion of social bonds due to globalization and technological advancements. Surah At-Tahrim, Verse 6, offers a significant Islamic framework for fostering family resilience. The central research question addresses how strategies for family resilience can be formulated in the contemporary context based on interpretations of Surah At-Tahrim, Verse 6, as presented in Tafsir Al-Azhar and Tafsir Ibnu Katsir. This study aims to analyze and formulate strategies for enhancing family resilience through a comparative examination of these two interpretations. Utilizing a qualitative methodology with a library research approach, the study employs content analysis, comparative analysis, and hermeneutic analysis to examine the interpretations offered by Tafsir Al-Azhar and Tafsir Ibnu Katsir. The findings reveal that both interpretations underscore the importance of family education, parental role modeling, protection against negative influences, and continuous spiritual development as fundamental strategies for fostering family resilience. However, a notable divergence is observed in their contextual approaches: Tafsir Al-Azhar exhibits a greater adaptability to modern challenges, while Tafsir Ibnu Katsir remains anchored in a more textual and traditional interpretive stance. The study concludes with the formulation of family resilience strategies that include strengthening spiritual foundations, fostering effective communication, building economic resilience, and adapting to technological changes. Contribution: This study enriches the field of Quranic exegesis and Islamic studies by highlighting the interplay between traditional and contextual interpretations, demonstrating how classical and modern tafsir can inform contemporary family resilience strategies.